Terminator. Dark fate [videorecording (Blu-Ray + DVD)] - Cameron, James, 1954-; Goyer, David S.; Rhodes, Justin; Hurd, Gale Anne; Eglee, Charles H.; Friedman, Josh (Paramount Home Entertainment, 2020)
An augmented human and Sarah Connor must stop an advanced liquid Terminator from hunting down a young girl, whose fate is critical to the human race.